Broadcast Media Reportage of Flooding Issues and Viewers` Expectations: Focus on South-South Nigeria - Rosemary Ebiere Governor; Jammy Seigha Guanah; Eloho Patience Oziwele; Ignatius Achilike Njoku; Ukamaka C. M. OZIOKO (Britain International for Academic Research (BIAR) Publisher, 2025)
The general objective of this study was to determine viewers’ perception of the angle of reportage of flooding issues by Nigerian Television Authority (NTA) and African Independent Television (AIT), focusing South-South, Nigeria. This paper employed quantitative method, and it anchored on the Agenda Setting theory. Data were obtained through a structured questionnaire. The data were analysed using mean scores, percentages, and frequency tables. The first finding revealed that majority of the respondent’s under study were frequently exposed to NTA and AIT. Findings further showed that respondents were exposed to the same array of content categories. It equally indicated the various ways the performance of NTA and AIT stations can be improved, from the perspectives of the viewers. Thus, the study concluded that NTA and AIT were credible news sources for residents in the South-South zone of Nigeria. It was recommended that, to maintain a high level of viewership, the television stations should endeavour to constantly raise the standards of their programmes with a view to meeting the expectations of audience members, especially when it concerns flooding that the South-South region is prone to. Also, television stations should report variety of flood stories from different angles, including reporting more from the perspectives of flood victims. Likewise, television stations should deploy a proactive reporting measure by reporting through the flooding circle, report more from victims’ experiences, balance reporting, provide in-depth analysis, and report more from the scenes of flooding.